CAUSES OF DEATH IN NEWBORN INFANTS ACCORDING TO AUTOPSY FINDINGS - Gh.- R. Walizadeh (Tehran University of Medical Sciences, 1987)
Autopsy findings in 138 newborn infants which died in a university nursery during 3 years are reviewed and discussed. 80 per cent were premature and small- for- date newborns of up to 2500 g birth weight. Most of these cases showed in addition to general prematurely signs, respiratory tract diseases such as atelectasia, amniotic fluid aspiration and hyaline membrane disease. The full term infants died mostly of malformations. In post neonatal period the cause of death was almost entirely infections such as bronchopneumonia, gastroenteritis and septicemia.